1987
DOI: 10.1577/1548-8659(1987)7<18:eotifw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbidity in Fresh Waters of Alaska

Abstract: Turbidity results from the scattering of light in water by organic and inorganic particles; however, high turbidities usually are caused by suspended inorganic particles, particularly sediment. For several Alaskan lakes, we found that the depth to which 1% of subsurface light penetrated had a strong inverse correlation with sediment‐induced turbidity. We also developed a model that describes the decrease in primary production in shallow interior Alaskan streams caused by sediment‐induced turbidity. Euphotic vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 57 publications
1
113
0
3
Order By: Relevance
“…Similar results were obtained with lime hydroxide suspensions (Sykora 1972). The relationship between suspended solids concentration (SSC) for placer-mining suspensions and turbidity (Lloyd et al 1987) indicates that an SSC of 50 mg litre L would produce a turbidity of c. 48 NTU. Growth rates may therefore be limited by turbidity levels over 48 NTU over long periods.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results were obtained with lime hydroxide suspensions (Sykora 1972). The relationship between suspended solids concentration (SSC) for placer-mining suspensions and turbidity (Lloyd et al 1987) indicates that an SSC of 50 mg litre L would produce a turbidity of c. 48 NTU. Growth rates may therefore be limited by turbidity levels over 48 NTU over long periods.…”
Section: Discussionsupporting
confidence: 67%
“…The navigation, upstream movement, distribution, predator avoidance, and feeding behaviour of fish can all be affected by increased turbidity in rivers (e.g., Alabaster & Lloyd 1982;Bruton 1985;Lloyd et al 1987;Newcombe & McDonald 1991;Gregory 1993;Waters 1995;Wood & Armitage 1997). In New Zealand, Ryan (1991) reviewed the effects of sediment pollution on the biota of streams and indicated that, although there was scope for concern, there was not enough information on the effects of suspended solids on native fish to protect the fish fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Increased suspended solids in the water column limits the availability of light for primary production, which can then impact primary consumers and potentially alter the food web interactions at higher trophic levels. Increased turbidity is associated with a decrease in the diversity of macroinvertebrates as well as decreases in fish species richness, predation, and reproductive success (Lloyd et al 1989;Henley et al 2000; Van de Meutter et al 2005). According to the Oregon Department of Environmental Quality, the Umatilla River exceeds benchmarks in turbidity measurements, making it water quality limiting (ODEQ 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Light is attenuated as it travels through the water column because of scattering and absorption of photons (Kirk 1994). Although light is attenuated in clear water, light attenuation increases systematically as suspended sediment concentration increases (Walmsley et al 1980;Lloyd et al 1987 Some suspended particles also absorb light, for instance, humic substances absorb blue light and thus impart yellow colours to waters, whereas clear waters tend to be blue-green due to the differential absorption of particular light wavelengths (Kirk 1985). In general, large particles rapidly settle out of the water column and, consequently, those that dominate light attenuation tend to be 0.2 -5 μm for minerals and 1 -20 μm for organic particles (Kirk 1994).…”
Section: Turbidity Suspended Sediment and Water Claritymentioning
confidence: 99%